2012
DOI: 10.1521/ijgp.2012.62.3.418
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Improvement in Coping Skills Following Multimodal Treatment in War Veterans with Chronic PTSD

Abstract: Due to the long-lasting and resistant symptoms characteristic of chronic combat posttraumatic stress disorder (PTSD), its treatment is complex and often requires a tailored therapeutic approach incorporating both psychotherapy and pharmacotherapy. A multimodal approach of psychoeducative, sociotherapeutic, and dynamically oriented trauma-focused groups is described. We assessed the short- and long-term effectiveness of this therapeutic program by monitoring its impact on PTSD symptoms, depression, neurotic sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Perhaps the best grounds for proposing that a 5-HT dysfunction exists in PTSD resides in the beneficial treatment effects of SSRIs, which, to date, have already been established as the first-line pharmacotherapeutic agents for treating acute and chronic PTSD. However, SSRIs largely have disadvantages including delayed onset of action, partial response with residual symptoms or non-response, and severe side effects (e.g., loss of sexual drive, gastrointestinal effects, changes in body weight), which limit their utility and indicate a major unmet medical need to explore more promising treatment approaches in PTSD [1117]. …”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the best grounds for proposing that a 5-HT dysfunction exists in PTSD resides in the beneficial treatment effects of SSRIs, which, to date, have already been established as the first-line pharmacotherapeutic agents for treating acute and chronic PTSD. However, SSRIs largely have disadvantages including delayed onset of action, partial response with residual symptoms or non-response, and severe side effects (e.g., loss of sexual drive, gastrointestinal effects, changes in body weight), which limit their utility and indicate a major unmet medical need to explore more promising treatment approaches in PTSD [1117]. …”
Section: Introductionmentioning
confidence: 99%
“…Neither sampled U.S. military veterans nor included control groups. Britvic ́et al (2012) observed significant reductions in PTSD and depression posttreatment in a sample of Croatian veterans, but gains were not maintained at follow-up. The dropout rate in this study was 17%.…”
Section: Mmgts For Ptsdmentioning
confidence: 88%
“…Training in trauma-focused CBT and EMDR is offered to practitioners, but this is not fully integrated into the helping system. With the existing high level of competencies in dynamic psychotherapy and psychopharmacology (Britvić et al, 2012), the challenge remains to develop a more stepwise approach to trauma-informed services, increase public awareness of risk and resilience factors, and to expand treatment choices to include evidencebased trauma-focused therapies and make them more available to the general populations in need. The Croatian Society for Traumatic Stress (CSTS) has been working on this challenge since it was founded in 2011 by organizing training workshops.…”
Section: Psychotraumatology In Croatiamentioning
confidence: 99%